IMPLEMENTASI PEMBELAJARAN IBADAH SHALAT BERBASIS E-LEARNING MANAGEMENT SYSTEM PADA ANAK TUNAGRAHITA DI SLB-C NEGERI PEMBINA PROVINSI KALIMANTAN SELATAN - Mahmudah Mahmudah; Elissa Elissa (CV. ADIBA AISHA AMIRA, 2022)
This online learning is a new phenomenon which has never happened before. In this online learning, educators utilizing internet technology as access to learning by using media-based E-learning Management System (LMS) as a application device used. All levels of education feel the impact From the implementation of online learning, one of them is a school for children with special needs. Good implementation of online learning will help achieve educational goals, especially in learning prayer for mentally retarded children. The purpose of this research is to knowing the implementation of LMS-based prayer learning for children mentally retarded at the SLB-C State of the coach, besides that it is also to find out the factors that supports and hinders the implementation of prayer learning LMS-based in the environment of people with mental retardation SLB-C Pembina State. This research is a field research (field research). With a qualitative approach, the field research is descriptive, namely: describe the actual reality on the ground qualitative approach is a phenomenon-oriented approach and natural phenomena. The conclusions of this study are based on the analysis of the data obtained is the implementation of LMS-based prayer learning for children mental retardation in SLB-C Pembina State of South Kalimantan Province, that the teacher PAI has given the best in the learning process of prayer that is conducted online, using LMS-based media. Seen from the efforts made by educators in planning, implementing and evaluation. By using LMS-based media in the form of the WhatsApp application, groups and modules. It turns out that in the application of learning with using the LMS there are supporting factors such as; technology/gadgets, educators and parents. Apart from the supporting factors it was also found that inhibiting factors such as; internet access and limited mastery of technology.